Reviewing the effectiveness of reward and punishment in improving employee performance in Jabodetabek - Alam, Muzidan Bahrul; Kamal, Ibnu Albab (International Journal Labs, 2024)
Human resource management involves acquiring, developing, and using human resources to support business goals. Qualifying, rewarding, and punishing employees is crucial for personal growth and professional development. Companies should empower their human resources and implement fair rewards and punishments to improve employee performance. In Indonesia's Jabodetabek region, employee performance is crucial for business growth. Employers must focus on incentives, sanctions, and work discipline to maintain or improve performance. This research examines the effectiveness of rewards and punishments in improving employee performance in the Jabodetabek area. Using the qualitative approach, the study found that companies provide rewards to employees who excel in accordance with company regulations. Sanctions are used to prevent future violations and prevent others from doing the same. Motivational factors and performance satisfaction are crucial in establishing a fair reward and punishment system. The study concludes that effective rewards and punishments can improve employee performance, highlighting the importance of a fair and effective approach in business management.